2010
DOI: 10.1111/j.1744-7917.2009.01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age at mating on the reproductive performance of Parthenium beetle, Zygogramma bicolorata (Coleoptera: Chrysomelidae)

Abstract: Age-specific mating incidence, sexual maturation and effect of age at mating on reproductive performance of the Parthenium beetle, Zygogramma bicolorata Pallister, was studied. Based on 50% mating incidence the calculated age of sexual maturation of males and females was 10.5 and 11.1 days, respectively, which was not statistically significant. However, on the basis of age at first mating, that is, sexual maturity, females matured 2 days earlier than males. Fecundity, pre-oviposition, oviposition and post-ovip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…The early commencement of mating in the presence of potential male competitors has also been reported in previous studies (Krupa and Sih 1993;Jormalainen et al 1994;Dick and Elwood 1996;Clutton-Brock et al 1997). Among age groups, the delay in commencement of mating by old individuals may be attributed to the female assessment of male quality followed by mating avoidance with older males (Bonduriansky and Brassil 2002;Jones and Elgar 2004;Beck and Promislow 2007;Omkar et al 2010). The decreased mating performance of old males has also been reported in other Coccinellidae species (Bista and Omkar 2015).…”
Section: Discussionsupporting
confidence: 73%
“…The early commencement of mating in the presence of potential male competitors has also been reported in previous studies (Krupa and Sih 1993;Jormalainen et al 1994;Dick and Elwood 1996;Clutton-Brock et al 1997). Among age groups, the delay in commencement of mating by old individuals may be attributed to the female assessment of male quality followed by mating avoidance with older males (Bonduriansky and Brassil 2002;Jones and Elgar 2004;Beck and Promislow 2007;Omkar et al 2010). The decreased mating performance of old males has also been reported in other Coccinellidae species (Bista and Omkar 2015).…”
Section: Discussionsupporting
confidence: 73%
“…Associations between mating behaviour and the reproductive and progeny attributes of C. septempunctata (r 2 -values ≥ 0.50 have Pvalues < 0.05 and indicate strong associations between the parameters; while r 2 -values < 0.50 have P-values ≥ 0.05 and indicate weak associations between the parameters). & Brassil, 2002;Beck & Promislow, 2007;Omkar et al, 2010). In contrast, there are studies that report a high female preference for old males (Proulx et al, 2002;Avent et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As the studies on age-specific mating incidences in ladybirds (see Srivastava & Omkar, 2004;Omkar & Pervez, 2005;Omkar et al, 2010;Omkar & Singh, 2010) indicate that middleaged mates have the highest fecundity and egg viability, and their offspring develop fastest; we hypothesized that: (i) under choice-test conditions, middle aged males / females would prefer middle aged partners rather than young and old partners, and (ii) middle aged partners would be more likely to mate, and their reproductive attributes and the development and survival of their offspring would be better than that of young and old partners.…”
Section: (Ii) Effect Of Mate Choice On Mating Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Ageing not only reduces the physiological integrity of structures and functions in insects (López‐Otín et al, 2013) but also affects the distribution of triglycerides, proteins and glucose in their body (Baumann & Chen, 1968; Butterworth & Bodenstein, 1968) and, consequently, their reproductive output. Studies assessing reproductive output in the Parthenium beetle, Zygogramma bicolorata Pallister have revealed that females that mate at an early or middle age have higher fecundity, longer oviposition periods and maximum life span than the females that mate at a later age (Omkar et al, 2010; Patel, Bhusal, et al, 2020). The offspring of such females also develop faster and survive longer than those of old females (Pandey & Omkar, 2013).…”
Section: Introductionmentioning
confidence: 99%